Digital craftsmanship spirit: informal tactics and the negotiation of platform power in China - Yue, Wenwen (Frontiers in Communication, 2025)
The platformization of social media has reconfigured creative labor globally, yet its dynamics unfold with distinct intensity in China’s unique digital ecosystem, characterized by state-market hybrid governance and algorithmic collectivism. In this study, we draw on 19 months of embedded fieldwork and in-depth interviews with 20 content creators, to examine how young Chinese bloggers deploy informal manipulations—tactical practices that resist and repurpose platform constraints. The result reveals a dialectical dynamic wherein these grassroots tactics simultaneously sustain platformization and cultivate creative agency, functioning as critical mechanisms for mediatization. Crucially, We identify the emergence of digital spiritual artisanship—a psychosocial process through which creators reconcile labor alienation with self-actualization through culturally-inflected practices of self-cultivation and community-building. Our work advance platform labor theory by conceptualizing informal resistance as co-constitutive of platform evolution, theorizing “Digital Craftsmanship Spirit” as a culturally distinct survival strategy under algorithmic collectivism, and mapping China’s unique governance model onto global digital labor debates.